History of the violin - Dahl, Inga Josephine (My University, 1898)
Introduction: No instrument ever has been, or ever will be invented capable of even approaching the violin in extraordinary power and variety of expression. It is considered the one perfect instrument; for a piano cannot be tuned perfectly, and a flute that will play in tune on all of its keys has never been invented. This instrument is more nearly a growth than an invention.
Citation: Dahl, Inga Josephine. History of the violin. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Instrument; Violin; Expression; Tune; Theses; Manuscripts (documents)